Encouragement of Women Teachers by means of Gender-conscious Educational Leadership: Viewpoints from NEP 2020 and Savitribai Phule - Adhikari, Gopal; Mantri, Bidhan; Amit Adhikari (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
Even while women's involvement in the teaching field is growing, unequal leadership representation and decision-making power continue to be fairly major. This study investigates how gender-conscious leadership helps women teachers to become empowered in the Indian educational scene. Using the theoretical inheritance of Savitribai Phule and the policy goals of National Education Policy 2020, the study uses a qualitative interpretative framework based on thematic analysis and document analysis. The results indicate that women teachers' professional agency, participation, and identity can all be improved by leadership techniques sensitive to gender dynamics. Entrenched socio-cultural standards and institutional restrictions, however, keep fair leadership chances back. The research highlights Phule's emancipatory vision's ongoing relevance in influencing inclusive educational leadership in accordance with current policy changes. It offers suggestions for including gender-sensitive leadership approaches into institutional management and teacher training.